الاستبداد السياسي وأثره في تخلف المسلمين عند عبد الرحمن الكواكبي ومحمد عبده: دراسة وصفية تحليلية مقارنة - أبو النصر، أحمد بن عبد الخالق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study deals with the concept of tyranny, its forms and contributing factors, effects on human life, impact on the movement of peoples and its role in the backwardness of the Muslim society. The thoughts of Abdul Rahman Al Kawwakibi and Mohamad Abduh, two prominent Muslim thinkers in the 19th century, are examined as the basis for this research. It also deals with the concept of power and the nature of the relationship between the ruler and the ruled, the adopted approach to confront tyranny and disposal of them. After presenting their ideas according to the analytical descriptive approach, the researcher undertook a comparative study of the ideas of these two thinkers to identify the similarities and differences between them on the subject of tyranny and how Muslims could get rid of it or, at least, not to allow it to take place. Of the two thinkers, this research takes side more with al-Kawatibi. Al-Kawakibi had been directly affected by despotism and fought fiercely against it and it did not damper his concern on the state of the ummah. Abdul Rahman al-Kawakibi believes that proper education cannot take place under tyranny and, for him, has directly been responsible in the backwardness of the Muslim society.